Análise crítica do plano diretor como instrumento de concretização ao direito à moradia em Fortaleza-Ce: um estudo sobre os primeiros dez anos de vigência do PDPFOR - Barbosa, Guilherme Bezerra (2021)
This research is built on the assumption that the 2009 Participative Master Plan of Fortaleza did not work as a tool to implement the fundamental right to housing in the city in the way this fundamental right is described by the 1988 Federal Constitution and by international treaties. From that assumption, a starting question is stated and initial hypothesis are formulated, which are related to the inquiry on what are the reasons by which the Master Plan of Fortaleza was not successful in fulfilling one of its constitutional goals: to secure that Fortaleza municipality, through urban policies, could execute the ideals and directives related to the right to housing as required by law. This work is the result of research developed through a case study, sited within the borders of Fortaleza municipality and in the first ten years of validity of the 2009 Participative Master Plan of Fortaleza, which is the maximum time span established by the City Statute for municipalities to review their master plans. The research that resulted in this dissertation is both theoretical and empirical because it brings a critical theoretical analysis on the right to housing, which is the foundation for the interpretation of the data, collected from Fortaleza municipality and from the Federal Government, regarding the application of the urban policy and land regularization legal instruments established by the City Statute and by the master plan of Fortaleza. This work was also made through participatory action research, anchored in a concept of law obtained with the use of the theoretical basis of dialectical materialism aiming for a broad and critical analysis of the 2009 Participative Master Plan of Fortaleza as an instrument of urban policies directed to guarantee access to housing. This research applies as well techniques of hypotetic deductive methodologies of research with the goal to extract lessons from a specific case study. After five chapters of exposition of the results obtained with this research, final considerations are proposed as additions to the debates and discussions held by civil society organizations that fight for the right to housing and the right to the city, regarding the future of the production of social interest housing in Fortaleza.